Unmasking Guion-Almeida syndrome: clinical and genetic insights from a 3-year-old with EFTUD2 mutation - Jacob, Linda; George, Jewel M.; Cherian, Carol S.; Abraham, Jacob (International Journal of Contemporary Pediatrics, 2026)
Guion-Almeida–type mandibulofacial dysostosis is an uncommon craniofacial syndrome arising from EFTUD2 mutations. Because its clinical phenotype overlaps significantly with other forms of mandibulofacial dysostosis, genetic testing is often required to secure a definitive diagnosis. Herein this report describes a 3 year 5-month-old male child who exhibited characteristic craniofacial dysmorphism, a surgically corrected cleft palate, speech delay, recurrent respiratory tract infections, and bilateral conductive hearing loss. His growth indices were persistently below −3 SD. Whole-exome sequencing identified a heterozygous pathogenic EFTUD2 variant, thereby confirming the diagnosis of MFDGA. The child received supportive respiratory management, nutritional rehabilitation, and continued speech and hearing therapy. Follow-up evaluation demonstrated spontaneous closure of a previously noted muscular ventricular septal defect. Ongoing multidisciplinary care was recommended to comprehensively address craniofacial, developmental, and systemic concerns. This case underscores the pivotal role of molecular diagnostics in distinguishing MFDGA from phenotypically similar craniofacial disorders and highlights the importance of coordinated, long-term multidisciplinary management throughout childhood.